The Gender Gap in Informal Child Care: Theory and Some Evidence from Italy - Francesca Barigozzi; Helmuth Cremer; Chiara Monfardini (Center for Economic Studies and ifo Institute (CESifo), 2019)
Our model studies couples' time allocation and career choices, which are affected by a social norm on gender roles in the family. Parents can provide two types of informal child care: basic care (feeding, changing children, baby-sitting) and quality care (activities that stimulate children's social and cognitive skills). We obtain the following main results. Traditional mothers provide some informal basic care, whereas career mothers purchase full time formal basic care in the market. Informal basic care is too large and the group of career mothers is too small because of the social norm. Informal quality care is increasing in the couple's income and is provided in larger amount by mothers. We test the model's predictions for Italy using the most recent ISTAT “Use of Time” survey. In line with the model, mothers devote more time than fathers to both basic and quality informal care; more educated parents devote more time to quality informal care than less educated parents; more educated mothers spend more time in the labor market than less educated mothers.
Keywords: D13; H23; J16; J22; 330; social norms; gender gaps; women's career choices; basic and quality child care